2017
DOI: 10.1097/cej.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Screening colonoscopy volume and detection of colorectal neoplasms: a state-wide study from Bavaria, Germany

Abstract: Screening colonoscopy enables early detection of colorectal cancer and its precancerous lesions. The aim of this study was to assess the association of screening colonoscopy volume with colorectal neoplasm detection rate in routine practice. A registry-based study of individuals aged at least 55 years who underwent screening colonoscopy in Bavaria, Germany, between 2007 and 2009 was performed. Colorectal neoplasm detection rates (95% confidence intervals) were determined per physician. Physicians were grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In addition, we cannot assess detailed clinical information for the cause of an early repeat colonoscopy within 12 months. We defined high-volume facility (i.e., annual colonoscopy volume ≥200) based on some evidence, 16,17 but it may still be arbitrary as it was a criterion for an endoscopist, not a healthcare facility. In a German screening colonoscopy registry, the detection rate of any neoplasm was better for annual colonoscopy volume ≥200 than annual colonoscopy volume <50 (27.5% vs 21.9%, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we cannot assess detailed clinical information for the cause of an early repeat colonoscopy within 12 months. We defined high-volume facility (i.e., annual colonoscopy volume ≥200) based on some evidence, 16,17 but it may still be arbitrary as it was a criterion for an endoscopist, not a healthcare facility. In a German screening colonoscopy registry, the detection rate of any neoplasm was better for annual colonoscopy volume ≥200 than annual colonoscopy volume <50 (27.5% vs 21.9%, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In a German screening colonoscopy registry, the detection rate of any neoplasm was better for annual colonoscopy volume ≥200 than annual colonoscopy volume <50 (27.5% vs 21.9%, p<0.001). 16 Spanish Society of Gastrointestinal Endoscopy also recommended at least 200 annual screening colonoscopies to maintain colonoscopy quality in CRC screening. 17 In conclusion, the national volume of colonoscopy has been progressively increasing regardless of sex, age group, and healthcare facility types for the past 12 years in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, medical specialists who perform colonoscopy tend to perform a higher volume of procedures, 24,38 which may be a major driving force behind better quality and colorectal outcomes. 39,40 Some studies have found that despite volume or experience, GEs have superior quality outcomes. 11,41 Other studies have shown that primary care physicians have the ability to have comparable metrics with colonoscopy specialists with the appropriate training and support.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, detecting cancer at early stage and removing adenoma is a critical measure to reduce the incidence and mortality of colorectal cancer (CRC). [1,2] However, worldwide CRC is the second most common cancer in males (9%) and the third most common cancer in females (8%) with an estimated 1.2 million new cases per year, and ranks fourth in mortality with an approximately 0.5 million deaths annually [35] due to the lack of efficient diagnostic tools and effective therapy. Currently, colonoscopy based on biopsy or on endoscopic tissue characterization and classification in vivo using chromoendoscopy and Kudo classifications is main auxiliary examination for colorectal lesions.…”
Section: Introductionmentioning
confidence: 99%